Eggs Introduced Early in Complementary Feeding and Egg Specific IgE Antibodies: A Randomized Controlled Trial in Ecuador. (7th June 2021) - Chapnick, Melissa; Diaz, Jenna; Boshara, Arianna; Powers, Jennifer; Gibson, David; Gallegos-Riofrío, Carlos Andres; Stewart, Christine; Lutter, Chessa; Waters, William; Iannotti, Lora
Abstract: Objectives: The purpose of the study was to assess the safety of using eggs as a nutritional intervention for stunting in infants living in a rural indigenous community in Ecuador and to further understand the prevalence of egg allergy in this population. Methods: The Lulun Project was a randomized controlled trial conducted in a rural indigenous population in Ecuador. Infants age 6–9 months were recruited and randomly assigned to the intervention (1 egg/day; n = 80) or control (no intervention, n = 83) group. At baseline and end line, enumerators collected anthropometric, dietary intake, morbidity, and sociodemographic data along with blood samples. Symptoms of allergies were assessed, including rash, congestion, coughing or wheezing, and diarrhea. Children in the intervention group were monitored by the study team for allergy symptoms during consumption of the first study egg. All children were monitored for illness and allergy symptoms throughout the study. We used ELISA assays to determine serum anti-ovomucoid and ovalbumin IgE levels, a validated approach to identify "risk of" egg allergy. Results: 131 of the children had a sufficient serum sample to be analyzed for IgE levels. Ovomucoid levels were <0.35 kUA /L in all children. 57 paired samples were available, 1 of 51 in the control and 2 of 56 in the intervention group developed increased responses to ovalbumin during the study (0.51−1.04 kUA /L). For unpaired endline samples (n = 51), 3 of 25 in the control group and 2 of 26 in the egg group had increased ovalbumin responses (0.6–1.36 kUA /L). No child was removed from the study due to a reaction to eggs. Conclusions: These findings support the use of eggs as a safe option to improve growth and reduce stunting in this community in Ecuador. Our study's findings are in alignment with current guidelines that recommend introducing eggs early in the complementary feeding period, and the evidence that doing so does not increase the risk of developing an egg allergy. Funding Sources: The Mathile Institute for Human Nutrition, The Bill and Melinda Gates Foundation, and the Washington University in St. Louis Institute for Public Health Summer Research Program funded this study.